Unlocking melanoma Suppression: Insights from Plasma-Induced potent miRNAs through PI3K-AKT-ZEB1 axis - Pradeep Bhartiya; Apurva Jaiswal; Manorma Negi; Neha Kaushik; Eun Ha Choi; Nagendra Kumar Kaushik (Journal of Advanced Research)
Introduction: Melanoma is a rare but highly malignant form of skin cancer. Although recent targeted and immune-based therapies have improved survival rates by 10–15%, effective melanoma treatment remains challenging. Therefore, novel, combinatorial therapy options such as non-thermal atmospheric pressure plasma (NTP) are being investigated to inhibit and prevent chemoresistance. Although several studies have reported the apoptotic and inhibitory effects of reactive oxygen species produced by NTP in the context of melanoma, the intricate molecular network that determines the role of microRNAs (miRNAs) in regulating NTP-mediated cell death remains unexplored. Objectives: This study aimed to explore the molecular mechanisms and miRNA networks regulated by NTP-induced oxidative stress in melanoma cells. Methods: Melanoma cells were exposed to NTP and then subjected to high-throughput miRNA sequencing to identify NTP-regulated miRNAs. Various biological processes and underlying molecular mechanisms were assessed using Alamar Blue, propidium iodide (PI) uptake, cell migration, and clonogenic assays followed by qRT-PCR and flow cytometry. Results: NTP exposure for 3 min was sufficient to modulate the expression of several miRNAs, inhibiting cell growth. Persistent NTP exposure for 5 min increased differential miRNA regulation, PI uptake, and the expression of genes involved in cell cycle arrest and death. qPCR confirmed that miR-200b-3p and miR-215-5p upregulation contributed to decreased cell viability and migration. Mechanistically, inhibiting miR-200b-3p and miR-215-5p in SK-2 cells enhanced ZEB1, PI3K, and AKT expression, increasing cell proliferation and viability. Conclusion: This study demonstrated that NTP exposure for 5 min results in the differential regulation of miRNAs related to the PI3K-AKT-ZEB1 axis and cell cycle dysregulation to facilitate melanoma suppression.